Combined well path, submarine pipeline network, route and flow rate optimization for shallow-water offshore fields. (December 2020) - Almedallah, Mohammed K.; Branch, Gregory; Walsh, Stuart D.C.
Abstract: This paper presents an integrated approach to planning wellbore trajectory, submarine pipeline networks, routes and production for offshore shallow-water oil and gas fields. The method integrates the optimization of realistic drilling well paths, platform location and well allocation using a combination of Constrained Optimization by Linear Approximation (COBYLA) and Mixed Integer Linear Programming (MILP). It also optimizes the pipeline network layout using a separate MILP routine that compares and combines three types of pipeline connections, namely: star connections from multiple wellhead platforms to a central facility; subsea connections from platforms to a subsea tie-in point; or piggyback connections between the wellhead platforms themselves. Specific pipeline paths are found using a global graph-search method that is coupled with a local refinement to find the least-cost path. We demonstrate this pipeline path optimization by considering shallow-water offshore fields that include the presence of obstacles along the route. The pipeline network layout and route optimization steps are further integrated with techniques to estimate the production flow rate and optimal operating pressure across the resulting pipeline network. A case study is provided based on real conditions of Gulf of Mexico to test and validate the model, and to highlight the importance of the subsurface and surface integration for field development planning.